2017
DOI: 10.1111/imb.12354
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterizations of DNA methyltransferase 3 and its roles in temperature tolerance in the whitefly, Bemisia tabaci Mediterranean

Abstract: The Bemisia tabaci Mediterranean (MED) cryptic species is an invasive pest, distributed worldwide, with high ecological adaptability and thermotolerance. DNA methylation (a reversible chromatin modification) is one possible change that may occur within an organism subjected to environmental stress. To assess the effects of temperature stress on DNA methyltransferase 3 (Dnmt3) in MED, we cloned and sequenced BtDnmt3 and identified its functions in response to high and low temperatures. The fulllength cDNA of Bt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…A decreasing expression pattern was observed after short exposures to various temperatures. Additional research conducted in the whitefly Bemisia tabaci found that the expression of BtDnmt3 significantly decreased after exposure to higher temperatures (35°C and 40°C), while the chilling treatment increased expression (Dai et al, 2018). Besides insects, the zebrafish host different expression patterns in different development stages, and a similar result was observed at bud stages (Campos, Valente, & Fernandes, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A decreasing expression pattern was observed after short exposures to various temperatures. Additional research conducted in the whitefly Bemisia tabaci found that the expression of BtDnmt3 significantly decreased after exposure to higher temperatures (35°C and 40°C), while the chilling treatment increased expression (Dai et al, 2018). Besides insects, the zebrafish host different expression patterns in different development stages, and a similar result was observed at bud stages (Campos, Valente, & Fernandes, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Hence, we speculated that DNA methylation plays an important role in M. separata 's environmental adaptation and development. Relevant research conducted on the invasive insect whitefly Bemisia tabaci (Gennadius), found that both BtDnmt1 and BtDnmt3 play an essential role in the insect's temperature tolerance capacity (Dai et al, 2017; Dai, Lü, Wang, Liu, & Wan, 2018). Therefore, in this study, the full length of the MsDnmt1 gene complementary DNA (cDNA) sequence was cloned and analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous studies [40,42], we selected 0, 12, 35, and 40 • C for short-term temperature stress treatments. Owing to research found that adult age was associated with different responses to thermal tolerance [47], we standardized adult age using only newly emerged whiteflies that were younger than 3 h. MEAM1 adults were placed together in a 1.5 mL centrifuge tube, then the tubes were placed in a constant-temperature environment (0, 12, 35, and 40 • C) for 1, 3, and 5 h. Adults maintained at 26 • C served as a control group.…”
Section: Temperature Stress Treatmentmentioning
confidence: 99%
“…Double-stranded RNA (dsRNA) used in this study was synthesized using the MEGAscript T7 High Yield Transcription Kit (Ambion, Austin, TX, USA) with gene-specific primers (Table 1). Then, the ISWI dsRNA was diluted to 0.4 µg/µL in a 10% sucrose solution for further feeding treatment (for detailed methods, refer to References [42,48]). Simultaneously, we set control groups including untreated whiteflies, those fed with eGFP-specific dsRNA (dseGFP), and those fed with 10% sucrose.…”
Section: Rna Interferencementioning
confidence: 99%
“…Dynamic changes in DNA methylation present a specific pattern in tissues or cell types. Epigenetic mechanisms may play an important role in the formation of heat acclimation and the changes in mitochondrial respiratory chain (OXPHOS) (Dai et al, 2018). However, few studies have been conducted on the relationships between genetic and epigenetic regulations under heat stress.…”
Section: Introductionmentioning
confidence: 99%